Optimization of SARS-CoV-2 culture from clinical samples for clinical trial applications - Dominic Wooding; Kate Buist; Alessandra Romero-Ramirez; Helen Savage; Rachel Watkins; Daisy Bengey; Caitlin Greenland-Bews; Caitlin R. Thompson; Nadia Kontogianni; Richard Body; Gail Hayward; Rachel L. Byrne; et al. (mSphere)
ABSTRACT Clinical trials of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) therapeutics often include virological secondary endpoints to compare viral clearance and viral load reduction between treatment and placebo arms. This is typically achieved using quantitative reverse-transcriptase PCR (RT-qPCR), which cannot differentiate replicant competent virus from non-viable virus or free RNA, limiting its utility as an endpoint. Culture-based methods for SARS-CoV-2 exist; however, these are often insensitive and poorly standardized for use as clinical trial endpoints. We report optimization of a culture-based approach evaluating three cell lines, three detection methods, and key culture parameters. We show that Vero-angiotensin-converting enzyme 2-transmembrane serine protease 2 cells in combination with RT-qPCR of culture supernatants from the first passage provides the greatest overall detection of Delta viral replication (22 of 32, 68.8%), being able to identify viable virus in 83.3% (20 of 24) of clinical samples with initial Ct values of <30. Likewise, we demonstrate that RT-qPCR using culture supernatants from the first passage of Vero human signaling lymphocytic activation molecule cells provides the highest overall detection of Omicron viral replication (9 of 31, 29%), detecting live virus in 39.1% (9 of 23) of clinical samples with initial Ct values of <25. This assessment demonstrates that combining RT-qPCR with virological endpoint analysis has utility in clinical trials of therapeutics for SARS-CoV-2; however, techniques may require optimization based on dominant circulating strain.IMPORTANCERT-qPCR is commonly used for virological endpoints during clinical trials for antiviral therapy to determine the quantity and presence of virus in a sample. However, RT-qPCR identifies viral RNA and cannot determine if viable virus is present. Existing culture-based techniques for SARS-CoV-2 are insensitive and not sufficiently standardized to be employed as clinical study endpoints. The use of a culture system to monitor replicating viruses could mitigate the possibility of molecular techniques identifying viral RNA from inactive or lysed viral particles. The methodology optimized in this study for detecting infectious viruses may have application as a secondary virological endpoint in clinical trials of therapeutics for SARS-CoV-2 in addition to numerous research processes.